Comparing carbide sludge-ground granulated blastfurnace slag and ordinary Portland cement: different findings from binder paste and stabilized clay slurry - Li, Wentao (2022)
This experimental study investigated the use of combined industry by-products, carbide sludge (CS) and ground granulated blast-furnace slag (GGBS), to replace ordinary Portland cement (OPC) for the stabilization of clay slurry, aiming to increase the stabilization efficacy, reduce the cost, and mitigate the environmental impacts associated with OPC production and disposal of industrial by-products. To better understand the stabilization mechanisms, properties of CS-GGBS and OPC stabilized clay slurry are systematically evaluated and compared. Test results indicate that the unconfined compressive strength (UCS) of the optimum CS-GGBS-stabilized clay slurry is 2–4 times that of the corresponding OPC-stabilized clay slurry. However, the strength of OPC paste is 1.3–1.4 times that of the optimum CS-GGBS paste. Due to the ultra-high water content and the active clay minerals, larger amounts of Ca(OH)2 are required to reach the same pH of pore water in stabilized clay slurry specimens than in the paste. This is responsible for the greater optimum CS/(CS + GGBS) ratio in the stabilized clay slurry than in the paste. OPC hydrates much faster and consumes more water than CS-GGBS during specimen preparation, resulting in a much lower void ratio and higher strength of OPC paste. For the stabilized clay slurry, the binder contents are very low and the water-to-binder ratio is hence very high, and thus the effect of binder hydration rate on the void ratio is insignificant. The remarkably different strength discrepancy between both types of stabilized clay slurry is not attributed to the slightly different void ratio, but due to the significantly different microstructures formed in the stabilized materials. The findings in this study contribute to a deep insight into the strength development of stabilized clay-slurry type dredged material.